The influence of certain factors on the physical growth and development of a group of Dublin city children - Kent, M. P.; Sexton, J. J. (Statistical and Social Inquiry Society of Ireland, 1973)
This paper presents the results of an inquiry into the influence of a number of social factors on certain growth and development parameters, based on an investigation of 412 Dublin city children aged between four and seven years, carried out in 1971. The social factors considered in this paper are size of family, standard of home conditions and occupation of father while the criteria used to measure child growth and development are height and weight. Other factors of more medical interest, such as birth weight, length of stay in hospital etc., were also studied and other measurements, also of a more medical character (such as skinfold thickness), were also taken in the course of this inquiry; the results of these analyses will be presented elsewhere.
Read before the Society, 18 May 1973
Keywords: Public health; Child health; Physical development; Social conditions; 314.15